Urgensi Penilaian Kesehatan Bank dan Tax Avoidance pada Kinerja Keuangan Perbankan Syariah - Wahyu Tri Susilowati; Baldric Siregar (Jurnal Akuntansi)
This study aims to examine the urgency of assessing bank soundness and tax avoidance on the financial performance of Islamic banks in Indonesia. This study uses Commercial Islamic Banks registered with the Financial Services Authority (OJK) which releases financial statements for the 2015-2020 period with a total of 72 data. This study uses multiple linear regression analysis techniques. The sampling technique used in this research is purposive sampling. The results of this study prove that the financing to deposit ratio (FDR) and operating costs of operating income (BOPO) have a negative effect on the financial performance of Islamic banks, while tax avoidance has a positive influence on the financial performance of Islamic banks. The hope is that Islamic banks can earn high profits if they succeed in carrying out efficiency in various fields. In addition, Islamic banks are also considered to be able to manage the costs they incur properly because they can generate high profitability. This study provides empirical data related to the analysis of the effect of bank health and tax avoidance by using multiple linear regression analysis approach. In addition, the research data used are general Islamic banks, the latest data is during 2015-2020. The research sample used is general Islamic bank data that has been registered with the Financial Services Authority (OJK).